Kinematic and kinetic comparisons of elite and well-trained sprinters during sprint start - Slawinski, J.; Bonnefoy, A.; Leveque, J. M.; Ontanon, G.; Riquet, A.; Dumas, R.; Cheze, L. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to compare the main kinematic, kinetic, and dynamic parameters of elite and well-trained sprinters during the starting block phase and the 2 subsequent steps. Six elite sprinters (10.06-10.43 s/100 m) and 6 well-trained sprinters (11.01-11.80 s/100 m) equipped with 63 passive reflective markers performed 4 maximal 10 m sprint starts on an indoor track. An opto-electronic motion analysis system consisting of 12 digital cameras (250 Hz) was used to record 3D marker trajectories. At the times "on your marks," "set," "clearing the block," and "landing and toe-off of the first and second step," the horizontal position of the center of mass (CM), its velocity (XCM and VCM), and the horizontal position of the rear and front hand (XHand_rear and XHand_front) were calculated. During the pushing phase on the starting block and the 2 first steps, the rate of force development and the impulse (Fimpulse) were also calculated. The main results showed that at each time XCM and VCM were significantly greater in elite sprinters. Moreover, during the pushing phase on the block, the rate of force development and Fimpulse were significantly greater in elite sprinters (respectively, 15,505 +/- 5,397 N/s and 8,459 +/- 3,811 N/s for the rate of force development; 276.2 +/- 36.0 Ns and 215.4 +/- 28.5 Ns for Fimpulse, p <= 0.05). Finally, at the block clearing, elite sprinters showed a greater XHand_rear and XHand_front than well-trained sprinters (respectively, 0.07+/- 0.12 m and -0.27 +/- 0.36 m for XHand_rear; 1.00 +/- 0.14 m and 0.52 +/- 0.27 m for XHand_front; p <= 0.05). The muscular strength and arm coordination appear to characterize the efficiency of the sprint start. To improve speed capacities of their athletes, coaches must include in their habitual training sessions of resistance training.